Colombian informal city (2007)
This article briefly display the results of the analysis and characterization of formation, transformation and urban consolidation processes in informal originated neighborhoods –urban unities– in the 90’s, in Colombia main cities, by analyzing the participation of State, community and private initiative acting as social agents and so the interactions established with the components of economic, juridical - political and institutional structures as social totality integrated to the city. It also analyzes other characteristic aspects of this sort of Latin American urban processes as: the participation of social agents in the origin and formation of informal settlements and the processes of consolidation of the urban units and informal origin-low income housing in the cities of Bogotá, Medellín, Cali, Barranquilla, Cartagena, Bucaramanga Manizales, Pereira, Ibagué and Cúcuta. Some of the existing conditions of public services and social equipment operation are indicated too, as well as the ways of participation of social agents in its construction and operation within the informal city; aspects relative to the quality of life represented in the socio-economical conditions of inhabitants and the ways of obtaining, financing and construction of housing and improvement of urban units are related. Consequently, an emphasis on problems of mobility and forced-displacement and its impact on urban instances and on the configuration of the informal city is made in order to present elements that let to identify the communities’ cultural attitude towards city, urban units and environment. Finally, the main environmental problems generated by the implantation and development of these urban units and the environmental situation are recognized in the Colombian informal establishments.